Role of Women in Family Income Generation in Umuahia- North Local Government Area of Abia State - C. C., Ndubuaku; U.E., Nnubia (Journal of Home Economics Research, 2024)
This paper investigated the role of women in family income generation in Umuahia North Local Government Area of Abia State. Specifically, the study identified possible income generating ventures which women can engage in, determined the challenges that face women in promoting family participation in the ventures and finally suggested ways of surmounting the challenges. Questionnaire was used for data collection. Mean was used for data analysis. Major findings include: rendering eatery and beer palour services, farming, weaving bags and jewelries from local materials, among others as the ventures women can engage in. Role of women include: involving family members in the decision making, teaching family members the skills involved in the ventures, challenges to income generation include lack of proper skills, death of family members among others. Possible measures for surmounting challenges include being flexible in decision making, embarking on workshops and seminars.